The Heterogeneous Impacts of Business Cycles on Educational Attainment - Ernest Boffy-Ramirez (Institute for the Study of Labor (IZA), 2016)
In this study I examine the impact of fluctuations in the unemployment rate before high school graduation on educational attainment measured 30 years later. I find evidence that educational attainment is countercyclical, as found in other studies, but also find that the impact of the unemployment rate varies across the ability distribution. Using data from the 1979 National Longitudinal Survey of Youth, this analysis identifies individuals who are on the boundary between pursuing and not pursuing additional education. Exposure to a higher unemployment rate at age 17 is associated with higher educational attainment for men in the 60-80th quintile of the ability distribution. There is little to no evidence of an effect beyond this quintile – highlighting the heterogeneous impacts of higher unemployment on educational attainment.
Keywords: I2; I22; J1; J18; J24; 330; educational attainment; unemployment; heterogeneous impacts; ability distribution